DESIGNING AN ENGLISH FOR NUTRITIONISTS AND DIETITIANS’ CURRICULUM: A RESEARCH BY ADDIE APPROACH - Rezza Dewintha (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2022)
This paper addressed to the curriculum study expecially the focus on English for Nutritionists and Dietitians Curriculum.  This study used ADDIE approach; Analysis, Design, Develop, Implementation, and Evaluation. This approach will lead to learning objectives as mentioned in Nutritionist and Dietitian life. Based on the needs of the respondents, several things were found that underlie the curriculum changes. The respondent's need to learn English (70.5%) is to support lectures. A total of 55.2% of them implement their target language in lectures. They prefer to talk with friends (51.4%) on campus (99%), once a week (65.4%). Learning language by listening to music is preferred (61.9%). The difficulty in the percentage is the lack of vocabulary (61.9%). The skill that was less mastered by the respondents was speaking (62.5%) while those mastered by Reading (41.7%). Most of the respondents had difficulty during the discussion related to the lack of vocabulary (48.5%) and they solved the problem by understanding the topics discussed in the discussion (45.6%). Respondents assessed that the existence of correspondence was irrelevant to their needs so that they were considered less effective in realizing the vision and mission of the study program, and also did not answer the respondent's needs in terms of learning. The conclusion of this study was it’s important to examine the needs of students as a basis for fulfilling future job vocations and also to prepare graduates of health workers who were of value and can compete with other professional graduates.